Модель управления IT-стартапами - Козина, Ольга Андреевна; Стратиенко, Наталия Константиновна (НТУ "ХПИ", 2017)
Установлено, что существующие модели управления предприятием не вполне пригодны для применения к IT-стартапам. Показана необходимость разработки метода управления, который охватывал бы все стадии жизненного цикла стартапа. Проведен анализ причин смертности стартапов на различных стадиях их жизненного цикла. Разработанная модель управления стартапами базируется на модели Бережливый стартап и позволяет избежать многих его ограничений.

Decrease mortality of startups during first three years of existing is important task of economy of any country. It has been established that the existing methods of enterprise management have some disadvantages or limits for using in IT-startups management. Analysis of mortality reasons of startups in different stages of their life cycle has been carried out. The comparing of reasons why startups in different time intervals, in different areas of them functioning are failure showed that the run out of cash and the use of not viable business model are appeared mortality factors most often denoted by ex-leaders of startups. The model of startup management based on the lean startup model has been developed. Steps for management of startups along first two stages of their life cycle were added. We noted that it is important to select set of static points and changeable points of startup during process of formulation of business model. Steps to reduce the number of iterations in the method of lean startup are proposed.
Model of IT-startups Management
Keywords: IT-стартап; управление проектом; бизнес-модели; этапы жизненного цикла; инвестиции; бережливый стартап; IT-start-up; project management; business model; life cycle stages; investments; lean startup model